Spiradenoma With Adenoid Cystic Carcinoma-like Changes: A Case Series of This Rare Variant With a Potential Diagnostic Pitfall - Plaza, Jose A; Kastnerova, Liubov; Gru, Alejandro A; Dulmage, Brittany; Sangueza, Martin J; Kazakov, Dmitry V (The American journal of surgical pathology, 2023)
Spiradenomas are benign cutaneous adnexal neoplasms with sweat gland differentiation that can manifest a broad spectrum of histomorphologic appearances. While they show a characteristic histopathologic phenotype and clinical management involves surgical excision with a low risk of recurrence, there have been unusual histopathologic variants of spiradenoma reported, including cases with adenoid cystic carcinoma (ACC)-like changes. Primary cutaneous ACC is a low-grade malignancy presenting as a subcutaneous mass with the potential for local invasion, perineural invasion, and high rates of local recurrence after excision. The diagnosis of spiradenomas with ACC-like features can be challenging, especially when only the ACC-like component is present for evaluation. A retrospective analysis of 21 cases of spiradenoma with ACC-like changes were obtained from large academic institutions, was performed, and summarized below. All cases showed background of conventional spiradenoma, and the ACC-like areas represented a component in all lesions. The percentage of ACC-like component ranged from 5% to 40% in all cases. The ACC-like component was multifocal and without pleomorphism, perineural and/or vascular invasion, necrosis, or increased mitotic activity. MYB translocation and protein expression was studied in 16 cases by fluorescence in situ hybridization, polymerase chain reaction, and immunohistochemistry. All studied cases were negative for MYB / NFIB , MYB L1, and MYB F by fluorescence in situ hybridization and polymerase chain reaction and 3 cases were positive for MYB expression by immunohistochemistry. Our study expands on spiradenomas with ACC-like features that ought to be considered in the differential diagnosis of cutaneous neoplasms such as primary cutaneous ACC. Our results indicate that a thorough histopathologic inspection and strict application of well-defined histologic criteria are necessary to support the diagnosis of this unusual histopathologic variant. These tumors can be difficult to diagnose, and awareness of their histomorphologic spectrum will facilitate definitive diagnosis and avoid misdiagnosis with other conditions.
Keywords: Carcinoma, Adenoid Cystic; Sweat Gland Neoplasms; akrospirom; Acrospiroma; retrospektivní studie; Humans; nádory potních žláz; lidé; nádory kůže; hybridizace in situ fluorescenční; Retrospective Studies; Skin Neoplasms; adenoidně cystický karcinom; In Situ Hybridization, Fluorescence